(untitled) (Pedagogy of Higher and Secondary Education, 2009)
In the article there are determined main peculiarities of aesthetic perception as the professional property of a creative art teacher: personal, aesthetic-artistic, mental ones under modern conditions of joining Ukraine to the Bologne process. Eurointegration defines such perspective directions of formation of a future creative art teacher personality at a High Pedagogical Educational Institution as determination of a life art conception, emphasis on spiritual bases of being, development of the aesthetic requirements, idea, tastes, perception improvement of the artistic and pedagogical skill by means of experimentation with new ideas, directions, technologies, methods et.